The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/recycling6010018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recycled HDPE Plastic Additions on Concrete Performance

Abstract: This study examined HDPE (high-density polyethylene) plastic waste as an added material for concrete mixtures. The selection of HDPE was based on its increased strength, hardness, and resistance to high temperatures compared with other plastics. It focused on how HDPE plastic can be used as an additive in concrete to increase its tensile strength and compressive strength. 156 specimens were used to identify the effect of adding different percentages and sizes of HDPE lamellar particles to lower, medium, and hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
(62 reference statements)
3
21
0
1
Order By: Relevance
“…This has created inefficiency in production and consumption and generated a significant rate of waste [5]. Waste management has been a special focus for cities and their urban infrastructure, including in construction [6,7] In many developing countries, improper city waste management systems offer a focus for circular metabolisms, which, simultaneously, can help to increase the cities' resilience [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has created inefficiency in production and consumption and generated a significant rate of waste [5]. Waste management has been a special focus for cities and their urban infrastructure, including in construction [6,7] In many developing countries, improper city waste management systems offer a focus for circular metabolisms, which, simultaneously, can help to increase the cities' resilience [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirms that waste management could be one priority area for CE implementation in Indonesia at any city level. Here, our analysis interprets a city in its entirety as a living system with the dynamic ability to overcome the resource challenges in in order to function well [6]. Understanding this dynamic is important in getting to know how best to view a city in order to comprehend its structure and its urban living functions.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rahim et al, (2013), polyethylene plastic wastes are best utilized in cement, sand, aggregate, concrete, and other construction materials. It also helps in reducing the cost of concrete manufacturing (Rahim et al, 2013), and helps increase the strength, hardness, and resistance of concrete materials (Tamrin & Nurdiana, 2021) thus, increasing construction safety (Treceñe, 2019). The concrete workability indicates the consistency of the concrete mix during the process.…”
Section: Discussionmentioning
confidence: 99%
“…The concrete workability indicates the consistency of the concrete mix during the process. The use of plastics as additives to the concrete mixture has affected the compaction caused by the contact with the surface and the internal friction (Tamrin & Nurdiana, 2021). Further, considering that plastics are lightweight and resistant to weather, therefore, plastics are good additives materials for concrete.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the feasibility of introducing polymer waste into concrete mixtures to improve their physical and mechanical properties [2,3]. e technology of polymer household waste utilization by their mechanical recycling has been developed.…”
Section: Introductionmentioning
confidence: 99%